Development Process and Cognitive Testing of CARATkids - Control of Allergic Rhinitis and Asthma Test for Children - Borrego, LM (2014)
Background: Allergic rhinitis and asthma (ARA) are chronic inflammatory diseases of the airways that often coexist in children. The only tool to assess the ARA control, the Control of Allergic Rhinitis and Asthma Test (CARAT) is to be used by adults. We aimed to develop the Pediatric version of Control of Allergic Rhinitis and Asthma Test (CARATkids) and to test its comprehensibility in children with 4 to 12 years of age. Methods: The questionnaire development included a literature review of pediatric questionnaires on asthma and/or rhinitis control and two consensus meetings of a multidisciplinary group. Cognitive testing was carried out in a cross-sectional qualitative study using cognitive interviews. Results: Four questionnaires to assess asthma and none to assess rhinitis control in children were identified. The multidisciplinary group produced a questionnaire version for children with 17 questions with illustrations and dichotomous (yes/no) response format. The version for caregivers had 4-points and dichotomous scales. Twenty-nine children, 4 to 12 years old, and their caregivers were interviewed. Only children over 6 years old could adequately answer the questionnaire. A few words/expressions were not fully understood by children of 6 to 8 years old. The drawings illustrating the questions were considered helpful by children and caregivers. Caregivers considered the questionnaire complete and clear and preferred dichotomous over the 4-points scales. The proportion of agreement between children and their caregivers was 61%. The words/expressions that were difficult to understand were amended. Conclusion: CARATkids, the first questionnaire to assess a child’s asthma and rhinitis control was developed and its content validity was assured. Cognitive testing showed that CARATKids is well-understood by children 6 to 12 years old. The questionnaire’s measurement properties can now be assessed in a validation study.